Main Factors of Financing the Affairs of Cultural Centers - Khushvaktov Azizbek Sirojiddinovich (International Journal on Integrated Education, 2022)
The article discusses the importance and necessity of financing the activities of cultural centers operating in the system of the Ministry of Culture of the Republic of Uzbekistan. In particular, suggestions and recommendations were made to increase the rate of paid income and develop the prospects of cultural centers through the provision of cultural services to the population.